2010
DOI: 10.1007/s12289-010-0756-6
|View full text |Cite
|
Sign up to set email alerts
|

Hole expansion simulation of high strength steel sheet

Abstract: The deformation behavior of high-strength steel sheet during hole expansion is investigated both experimentally and analytically to clarify the effects of the material model (anisotropic yield function) on the finite element simulation of a hole expansion. The test material used in the hole expansion test is a dual-phase steel alloy with a tensile strength of 780 MPa. The elastic-plastic deformation behavior of the test material is precisely measured using biaxial tensile tests with cruciform specimens to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In literature, there are several experimental test methods that are used for determining the biaxial anisotropy like biaxial tension test [37] and disk compression test [38]. In the current study, the hole-expansion test was performed to advanced high strength TRIP 800 steel in order to determine biaxial anisotropy.…”
Section: Hole-expansion Testmentioning
confidence: 99%
“…In literature, there are several experimental test methods that are used for determining the biaxial anisotropy like biaxial tension test [37] and disk compression test [38]. In the current study, the hole-expansion test was performed to advanced high strength TRIP 800 steel in order to determine biaxial anisotropy.…”
Section: Hole-expansion Testmentioning
confidence: 99%
“…Under such a loading condition, the hole edge is subjected to uniaxial tension and the maximum strain is generated at the edge hoop, rendering the stretch limit sensitive to edge condition. Besides conical punch head tests, flat-top punch head tests (Hashimoto et al, 2010), as well as hemispherical punch head tests (Adamczyk et al, 1983) have also been reported in the literature. A few testing standards have already been established, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Previous authors have analysed the HER of different automotive alloys. Larour et al and Yoon et al analysed the widely used Dual Phase steels (DP) [13][14][15][16][17] , Krempaszky et al and Dünckelmeyer et al analysed the fatigue resistant Complex Phase steels (CP) [13,18,19] , Paul et al, Krawczyk et al and Choi et al analysed the high formability Transformation-Induced Plasticity steels (TRIP) [20][21][22] , other authors such as Xu et al analysed the second generation steels Twinning-Induced Plasticity (TWIP) [15,17,20,22] , up to the really high strength Martensitic steels (MS) analysed by Chen et al [23]. In addition, lower strength automotive steels such as stainless steels [24] and Extra Deep Drawing (EDD) steels [20,25] were also investigated by Li et al and Stachoswicz. Regarding the mechanical properties, Narayanasamy et al reported that with higher ultimate tensile strengths lower HERs are obtained [26] .…”
Section: Introductionmentioning
confidence: 99%